A Maqāṣid Al-Sharī‘Ah Perspective on Illegal Mountain Mining: Environmental Destruction and the Violation of Public Property - Abdul wasik; Saifullah Saifullah (Journal of Innovative and Creativity, 2025)
Illegal mining has emerged as a deeply troubling phenomenon due to its adverse effects on environmental degradation, the usurpation of public rights, and the threat it poses to the sustainability of natural resources. From the perspective of Maqāṣid al-Sharī‘ah, this practice is not only a violation of positive law but also contradicts the core principles of the five universal objectives of Islamic law, especially ḥifẓ al-nafs (protection of life), ḥifẓ al-māl (protection of property), and ḥifẓ al-bi’ah (protection of the environment) as a derived objective. This paper aims to analyze illegal mining using the approaches of uṣūl al-fiqh and maqāṣid al-sharī‘ah through a descriptive-analytical method grounded in both classical and contemporary literature. The findings indicate that illegal mining constitutes an act of ta‘addī (transgression) and ifsād (corruption), fundamentally opposing the objectives of Islamic law and necessitating the application of sadd al-dharā’i‘ (blocking the means) to prevent further harm. This article affirms the urgency of Islamic environmental jurisprudence (fiqh al-bi’ah) as an academic response to the ecological crisis caused by unethical exploitation of natural resources.